Software engineering and formal methods : 14th International Conference, SEFM 2016, held as part of STAF 2016, Vienna, Austria, July 4-8, 2016, Proceedings /: 14th International Conference, SEFM 2016, held as part of STAF 2016, Vienna, Austria, July 4-8, 2016, Proceedings. (2016) - Unknown
No abstract available